Use of mechanical circulatory support in patients with non‐ischaemic cardiogenic shock. (26th February 2023) - Schrage, Benedikt; Sundermeyer, Jonas; Beer, Benedikt Norbert; Bertoldi, Letizia; Bernhardt, Alexander; Blankenberg, Stefan; Dauw, Jeroen; Dindane, Zouhir; Eckner, Dennis; Eitel, Ingo; Graf, Tobias; Horn, Patrick; et al.
ABSTRACT: Aims: Despite its high incidence and mortality risk, there is no evidence‐based treatment for non‐ischaemic cardiogenic shock (CS). The aim of this study was to evaluate the use of mechanical circulatory support (MCS) for non‐ischaemic CS treatment. Methods and results: In this multicentre, international, retrospective study, data from 890 patients with non‐ischaemic CS, defined as CS due to severe de‐novo or acute‐on‐chronic heart failure with no need for urgent revascularization, treated with or without active MCS, were collected. The association between active MCS use and the primary endpoint of 30‐day mortality was assessed in a 1:1 propensity‐matched cohort. MCS was used in 386 (43%) patients. Patients treated with MCS presented with more severe CS (37% vs. 23% deteriorating CS, 30% vs. 25% in extremis CS) and had a lower left ventricular ejection fraction at baseline (21% vs. 25%). After matching, 267 patients treated with MCS were compared with 267 patients treated without MCS. In the matched cohort, MCS use was associated with a lower 30‐day mortality (hazard ratio 0.76, 95% confidence interval 0.59–0.97). This finding was consistent through all tested subgroups except when CS severity was considered, indicating risk reduction especially in patients with deteriorating CS. However, complications occurred more frequently in patients with MCS; e.g. severe bleeding (16.5% vs. 6.4%) and access‐site related ischaemia (6.7% vs. 0%). Conclusion: In patients with non‐ischaemic CS, MCS use was associated with lower 30‐day mortality as compared to medical therapy only, but also with more complications. Randomized trials are needed to validate these findings. Abstract : Use of mechanical circulatory support (MCS) in patients with non‐ischaemic cardiogenic shock (CS). CI, confidence interval; HR, hazard ratio.